Information technology and management - Thompson, Ronald L.; Cats-Baril, William L. (New York McGraw-Hill Irwin, 2003)
This book introduction to business processes and the information systems that can make these processes more effective. The book covers the traditional topics of information technology, information system components, and information system development. But it goes beyond this traditional coverage, showing how businesses function and how information systems enable businesses to function more effectively.
Index: p. 516-537
Keywords: Quản trị kinh doanh